Synthesis of 2-Pyrrolidinones by Palladium-Catalyzed [3+2] Cycloaddition of Isocyanates - Kljajic, Marko; Schlatzer, Thomas; Breinbauer, Rolf (Synlett, 2019)
Pd/DPEphos catalyzes the [3+2] cycloaddition of various alkyl isocyanates with 2-acetoxymethyl-3-allyltrimethylsilane as a synthetic equivalent of trimethylenemethane (TMM). Taking advantage of 2-acetoxymethyl-3-allyltrimethylsilane acting both as nucleophile as well as electrophile this reaction gives a convenient access to 5-ring lactams with an exocyclic alkene moiety. The formation of the β,γ-unsaturated 2-pyrrolidinones occurs without olefin isomerization and without epimerization of the stereogenic centers. Mechanistic investigations suggest an initial N-allylation of the isocyanate followed by nucleophilic ring closure furnishing the desired 2-pyrrolidinones.
Keywords: allyl silanes; cycloaddition; heterocycles; isocyanates; lactams; palladium; Tsuji–Trost allylation